EXAMINING THE COGNITIVE STRUCTURES OF TEACHER CANDIDATES ON THE ENVIRONMENTAL ETHICS CONCEPT - Güher, Ebru; Açıkses, Erdal (My University, 2019)
Environmental ethics, which investigates human's moral relations with the environmentphilosophically, significantly affect the attitudes and behaviors of the individual towards theenvironment. This study aims to determine how teacher candidates form a link in their cognitivestructures concerning the concept of environmental ethics and to evaluate the parts comparativelyso that the established network of knowledge can be resolved. The study group consists of 150university students whose social studies teachers, science and technology teachers and elementaryschool teachers are determined by the sample criteria of the 3rd and 4th grades of Siirt Universityat Education Faculty during the spring of the 2016-2017 academic year. Word association test wasused as a data collection tool in the study. In the analysis of the obtained data, a frequency tablegenerated from the responses given to the environmental ethics key concept was utilized. Besides,a network of concepts has been established to reveal the cognitive structures of the obtained dataand teacher candidates separately and as a whole. It has been determined that the concept of\"environmental ethics\" as a whole is derived from teachers' candidates in terms of environmentalethics when evaluated in terms of content and ethics. In terms of departments, social scienceteachers and prospective teachers who read in elementary school teacher are more abstract wordswith ethical meaning when they are evaluated in frequency, while candidates in science knowledgeuse more concrete words. When the frequency table of the teachers' candidates about the conceptof environmental ethics is examined, it has been determined that the social studies, elementaryschool, and science teacher candidates are inadequate in establishing scientific knowledge.
Keywords: Eğitim; Eğitim Araştırmaları; Çevre Bilimleri; Felsefe